2022
DOI: 10.26442/00403660.2022.03.201437
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of predictors of response to anti-IgE therapy in patients with severe atopic bronchial asthma in real clinical practice

Abstract: Introduction. Guidelines on Biological Therapy for Bronchial Asthma of the European Academy of Allergy and Clinical Immunology (EAACI) identified a number of controversial issues for additional outcome analysis using randomized clinical trials and data from routine clinical practice. In particular, there is unmet need to clarify algorithms for prescribing biologicals using predictors of response and its timing, taking into account risk factors and multimorbidity. Omalizumab is a recombinant humanized monoclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In addition, the rate of drug allergy was higher in patients who switched to mepolizumab due to omalizumab treatment failure. In a study by Fomina et al [25], the N-ERD history and blood eosinophil count were found to be higher in patients who did not respond to omalizumab treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the rate of drug allergy was higher in patients who switched to mepolizumab due to omalizumab treatment failure. In a study by Fomina et al [25], the N-ERD history and blood eosinophil count were found to be higher in patients who did not respond to omalizumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the rate of CRSwNP was seen to be significantly higher in patients with severe asthma who were switched to mepolizumab due to omalizumab unresponsiveness. There are some studies in the literature suggesting that the rate of CRSwNP is high in patients with severe asthma who do not respond to omalizumab treatment [25,26]. In addition, the rate of drug allergy was higher in patients who switched to mepolizumab due to omalizumab treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Biological drugs can block specific immune pathways that limit the cascade determining inflammation, and for this reason, they are used in the treatment of severe forms of asthma [ 65 ]. Many monoclonal antibodies are currently approved for severe type 2 asthma in adults: omalizumab, mepolizumab, benralizumab, reslizumab and dupilumab [ 66 ].…”
Section: Efficacy and Effectiveness Of Covid-19 Vaccines In Pediatric...mentioning
confidence: 99%